ANALISIS SISTEM INFORMASI AKUNTANSI PENGGAJIAN GURU HONORER PEMERINTAH KABUPATEN ENDE: Studi Kasus Pada Dinas Pendidikan dan Kebudayaan Kabupaten Ende - Apriani, Chyntya; Thalib, Sabra B W; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2021)
This study uses a qualitative approach method, to describe the accounting information system of the honorary teachers payroll. And also the source of the used data is primary data. The data will be analyzed by descriptive analysis method. Based on the data analysis, it is concluded that the Government in regulating its operational activities has implemented an accounting information system and internal control over the payroll system using SIMDA and SIPD applications. All document data, namely SPP, SPPM, are inputted toto the Regional Financial and Asset Management Office of Ende Regency. However, in its implementation there are still run into delays in paying salaries. The cause of the late disbursement of the regional revenue and expenditure budget for the 2021 fiscal year is due to a change in the system. Initially the APBD disbursement system used the Regional Management Information System (SIMDA) to the Regional Government Information System (SIPD), then there was a transition to the use of new applications in the budget disbursement process in which the budget post for honorary staff was returned to their respective fields where the honorary staff/honorary teachers work, In addition, the payment process uses Inventory Money (UP) or Change Money(GU) depending on the availability of funds at the time of disbursement of Inventory Money.